2006
DOI: 10.1007/s00134-006-0262-y
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of severe acute respiratory distress syndrome: role of extracorporeal gas exchange

Abstract: ECMO treatment does not predict mortality in patients with most severe ARDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
2
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 17 publications
3
48
2
4
Order By: Relevance
“…Complications are experienced by most of both cardiac and respiratory failure patients treated with ECMO, and patients with poor outcomes associated with worse outcome. 3,6,24,28,29 In our sample, mean age was significantly greater for patients who had a poor outcome in the total sample and cardiac subgroups, and age remained significantly associated with outcome for the cardiac subgroup in the regression analysis. We found that days of mechanical ventilator support trended higher in patients with a poor outcome (3 days vs 2 days), but was not significantly different between outcome groups either in the total sample or the cardiac subgroup.…”
Section: Resultsmentioning
confidence: 56%
“…Complications are experienced by most of both cardiac and respiratory failure patients treated with ECMO, and patients with poor outcomes associated with worse outcome. 3,6,24,28,29 In our sample, mean age was significantly greater for patients who had a poor outcome in the total sample and cardiac subgroups, and age remained significantly associated with outcome for the cardiac subgroup in the regression analysis. We found that days of mechanical ventilator support trended higher in patients with a poor outcome (3 days vs 2 days), but was not significantly different between outcome groups either in the total sample or the cardiac subgroup.…”
Section: Resultsmentioning
confidence: 56%
“…Ten studies fulfilled the inclusion criteria, including four RCTs (19)(20)(21)(22) and six observational studies (14,(23)(24)(25)(26)(27). No SYSTEMATIC REVIEW SYSTEMATIC REVIEW pediatric trials met the inclusion criteria, and, therefore, only adult patients were included in all analyses.…”
Section: Literature Searchmentioning
confidence: 99%
“…Among these, age9, 18, 21, 22, 23, 24 and SOFA score21, 22, 23, 24 were found to be particularly closely associated with hospital mortality and were independent prognostic factors in ARDS patients receiving ECMO support. Roch et al 22.…”
Section: Discussionmentioning
confidence: 96%